Polysaccharide-Based Carriers for Pulmonary Insulin Delivery: The Potential of Coffee as an Unconventional Source - Sara A. Valente; Guido R. Lopes; Isabel Ferreira; Miguel F. Galrinho; Margarida Almeida; Paula Ferreira; Maria T. Cruz; Manuel A. Coimbra; Cláudia P. Passos (MDPI AG, 2023)
Non-invasive routes for insulin delivery are emerging as alternatives to currently painful subcutaneous injections. For pulmonary delivery, formulations may be in powdered particle form, using carriers such as polysaccharides to stabilise the active principle. Roasted coffee beans and spent coffee grounds (SCG) are rich in polysaccharides, namely galactomannans and arabinogalactans. In this work, the polysaccharides were obtained from roasted coffee and SCG for the preparation of insulin-loaded microparticles. The galactomannan and arabinogalactan-rich fractions of coffee beverages were purified by ultrafiltration and separated by graded ethanol precipitations at 50% and 75%, respectively. For SCG, galactomannan-rich and arabinogalactan-rich fractions were recovered by microwave-assisted extraction at 150 °C and at 180 °C, followed by ultrafiltration. Each extract was spray-dried with insulin 10% (w/w). All microparticles had a raisin-like morphology and average diameters of 1-5 µm, which are appropriate for pulmonary delivery. Galactomannan-based microparticles, independently of their source, released insulin in a gradual manner, while arabinogalactan-based ones presented a burst release. The microparticles were seen to be non-cytotoxic for cells representative of the lung, specifically lung epithelial cells (A549) and macrophages (Raw 264.7) up to 1 mg/mL. This work shows how coffee can be a sustainable source of polysaccharide carriers for insulin delivery via the pulmonary route.